2021
DOI: 10.1021/acs.chemmater.1c00715
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dissolution and Phase Transformation Mechanisms in Aqueous Zn/α-V2O5 Batteries

Abstract: Anhydrous α-V 2 O 5 was the first class of cathodes studied for rechargeable aqueous zinc-ion batteries (AZIBs), mainly due to its layered structure and high theoretical capacity. However, the poor cycle life of Zn/α-V 2 O 5 prevents it from being used as a practical cathode. A critical need for the advancement of high-capacity aqueous Zn/α-V 2 O 5 batteries is a better understanding of the degradation mechanisms in an α-V 2 O 5 cathode. Through a combined experimental and theoretical approach, we here report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 52 publications
3
88
0
Order By: Relevance
“…In AZIBs, however, α-V 2 O 5 is known to require long activation cycles, making it incompatible with practical use 21 . Recently, Huang’s group reported that α-V 2 O 5 undergoes a transformation from its original phase to hydrated vanadium pentoxide within the aqueous zinc electrolyte, and once transformed, it does not need the activation step anymore 44 . With these results in mind, we used a simple sol-gel method to synthesize the hydrated vanadium pentoxide (vanadium oxide xerogel, VOX) to obviate the need for the activation step and employed it as the cathode in an AZIB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In AZIBs, however, α-V 2 O 5 is known to require long activation cycles, making it incompatible with practical use 21 . Recently, Huang’s group reported that α-V 2 O 5 undergoes a transformation from its original phase to hydrated vanadium pentoxide within the aqueous zinc electrolyte, and once transformed, it does not need the activation step anymore 44 . With these results in mind, we used a simple sol-gel method to synthesize the hydrated vanadium pentoxide (vanadium oxide xerogel, VOX) to obviate the need for the activation step and employed it as the cathode in an AZIB.…”
Section: Resultsmentioning
confidence: 99%
“…2a ) did not exhibit any peaks related to the ZVO phase in any selected state in the first cycle, which implies that the ZVO phase did not form during the electrochemical charge /discharge process. Recently, the formation of the ZVO within the aqueous solution containing Zn ions was reported to be associated with the dissolution of vanadium pentoxide and the subsequent precipitation via the following reactions 44 . To establish whether this also applies to the VOX, a simple dissolution test was performed by immersing the VOX electrode in a 3 m Zn(OTf) 2( aq ) solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the energy range of 517 and 525 eV, two peaks corresponding to the spin-orbit of V2p 3/2 and V2p 1/2 are detected, which can be separated into two peaks of V 5 + and V 4 + . [15] The N1s XPS spectra of the V 2 O 5 /PANI is shown in Figure 1d, the four peaks at 402.3 401.0, 399.2, and 398.3 eV correspond to protonated imine species (À N=), protonated amine (À NHÀ ), benzenoid imine (À NH + À ) and quinonoid imine (À N + =), respectively. [16] These groups are expected to produce a semi-oxidized state, significantly enhancing the conductivity of PANI.…”
Section: Resultsmentioning
confidence: 99%